ICAM-directed vascular immunotargeting of antithrombotic agents to the endothelial luminal surface - Murciano, Juan Carlos; Muro, Silvia; Koniaris, Lauren; Christofidou-Solomidou, Melpo; Harshaw, David W.; Albelda, Steven M.; Granger, D. Neil; Cines, Douglas B.; Muzykantov, Vladimir R. (My University, 2003)
Drug targeting to a highly expressed, noninternalizable determinant up-regulated on the perturbed endothelium may help to manage inflammation and thrombosis. We tested whether inter-cellular adhesion mole cule-1 (ICAM-1) targeting is suitable to de liver antithrombotic drugs to the pulmonary vascular lumen. ICAM-1 antibodies bind to the surface of endothelial cells in culture, in perfused lungs, and in vivo. Proinflamma tory cytokines enhance anti-ICAM binding totheendotheliumwithoutinducinginternal ization. 125I-labeled anti-ICAM and a reporter enzyme( -Gal)conjugatedtoanti-ICAMbind to endothelium and accumulate in the lungs after intravenous administration in rats and mice. Anti-ICAM is seen to localize predomi nantly on the luminal surface of the pulmo nary endothelium by electron microscopy. We studied the pharmacological effect of ICAM-directed targeting of tissue-type plas minogen activator (tPA). Anti-ICAM/tPA, but not control IgG/tPA, conjugate accumulates in the rat lungs, where it exerts plasminogen activator activity and dissolves fibrin micro emboli. Therefore, ICAM may serve as a target for drug delivery to endothelium, for example, for pulmonary thromboprophy laxis. Enhanced drug delivery to sites of inflammation and the potential anti-inflam matory effect of blocking ICAM-1 may en hance the benefit of this targeting strategy